Truth in Language: Textual Data Analysis - Snukiškienė, Irena (Vilnius University Open Series, 2020)
The article presents Lithuanian linguistic cultural image of truth reconstructed from textual data. Textual data consists of contemporary and archaic (folklore and paremia) texts. The picture of truth distinguished from the textual data is highly philosophical, what proves the opinion that language is the reflection of a nation’s philosophy and worldview. Contemporary Lithuanian language reflects two main semantic aspects of truth: absolutism and relativism. Absolutism views truth as eternal and unique, forming the background of peoples’ lives. This type of truth usually has its source in religion. Subjectivism views truth as subjective and relative, depending on time, circumstances and opinions. The boundary between subjective truth and lie is very vague. This type of truth is never unique and has a pragmatic aspect which is either collective or individual. However, the dialogue of different sides is very important as it can help to achieve the final, objective truth. Epistemological aspect of truth is also salient. Two main aspects concerning truth cognition are scepticism and dogmatism. Cognition and knowledge is seen as the way to achieve the truth; however, sceptical question is raised whether truth cognition is possible at all. Dogmatism accepts certain facts or dogmas as naturally true. Truth is usually presented as unpleasant, painful, dangerous and unclear; however, it is highly important. Textual data also reflect a lot of opposites of truth: lie, unknown, myth, bluff, artificiality, half-truth, benefit.
Keywords: truth; linguistic worldview; textual data; linguo-cultural research